Bell's Palsy Post COVID-19 Vaccination: An Unwanted Occurence of Coincidence - Pramanasari, Indra; Chrissanty, Chrissanty (AKSONA, 2024)
Highlight: The COVID-19 vaccination is one of the methods used to combat the COVID-19 pandemic. Bell's palsy is one of the unwanted side effects of the COVID-19 vaccination. The benefits and protective impacts of the COVID-19 vaccine exceed the dangers.   ABSTRACT Introduction: TOne way to fight the COVID-19 pandemic is through vaccination. Indonesia widely uses a number of vaccines. The inactivated virus vaccine (Sinovac-CoronaVac), the recombinant adenovirus vector vaccine ChAdOx1-S/nCoV-19 (AstraZeneca), the mRNA-1273 vaccine (Moderna), and the BNT162b2 mRNA vaccine (Pfizer-BioNTech) are some of these. The COVID-19 vaccination has reported several cases of acute facial nerve paralysis as an adverse event. Case: A 34-year-old female patient complained of drooping lips to the left side and being unable to close the right eyelid three days after receiving the first dose of the COVID-19 vaccine inactivated virus type (CoronaVac). Physical examination revealed obesity, right lagophthalmos, and right peripheral facial nerve paralysis, but no extremity paresis. The patient was clinically diagnosed with Bell's palsy and received corticosteroid therapy. The patient's complaints improved after 2 weeks of treatment. Reports indicate that several types of COVID-19 vaccines have resulted in acute facial nerve paralysis. The mRNA-type COVID-19 vaccine led to the most widely reported cases of Bell’s palsy. The incidence of Bell's palsy after the COVID-19 vaccine is very rare. Conclusion: Overall, the advantages and protective effects of the COVID-19 vaccine outweigh the risks.